The Magical Strength of Nrimo and Gotong-Royong A Quick Response Report Following the May 27, 2006 Earthquake in Yogyakarta - Yuniarti, Kwartarini Wahyu (Faculty of Psychology, Universitas Surabaya, 2009)
People’s response and ways of coping to disasters vary across events. This quick response report aims to learn about the life reconstruction of the survivors within the 1st week following the 2006 Yogyakarta earthquake. Initial unstructured interviews and observations were used during the emergency phase, and followed up with a quick survey of 677 survivors. Descriptive analysis and follow-up interviews were undertaken to verify the results. During the first three days after the disaster, survivors seemed to be in a period of shock. They accepted the event as determined by God (nrimo=accepting). The survey showed more than 90% believed that God will help them, but also that more than 90% started doing something. Local slogans can be widely observed, e.g.,“Dlingo- Bangkit” (Revive-Dlingo!!). The local belief in nrimo seemed to yield positive energy, which enabled survivors to revive in a relatively short time. The “culture-of-waiting” seemed to function as a way to unify energy in “Gotong-Royong” (or mutual assistance). Respons dan cara menghadapi bencana sangat bervariasi dalam setiap kejadian. Studi “respons cepat” ini bertujuan untuk mempelajari proses kebangkitan kembali para penderita dalam minggu pertama setelah mengalami gempa bumi.Wawancara dan observasi tak-terstruktur dilakukan pada masa darurat, diikuti dengan survei cepat pada 677 orang yang terselamatkan. Analisis deskriptif dan wawancara verifikasi dilakukan setelah survei. Periode “terguncang” dialami pada 3 hari pertama. Masyarakat menerima kejadian tersebut sebagai sesuatu yang telah ditentukan oleh Allah (menerima = ”nrimo”). Hasil survei menunjukan bahwa lebih dari 90% percaya bahwa Allah pasti menolong mereka, bahkan lebih dari 90% telah melakukan sesuatu untuk bangkit kembali. Slogan “Dlingo Bangkit” banyak dijumpai di Desa Dlingo dan Turi. Tampaknya kepercayaan lokal dalam “nrimo” menyimpan energi positif, sedangkan “Gotong Royong” merupakan penyatuan energi positif dari para survivor, karenanya mereka bangkit dalam waktu yang relatif singkat.